Understanding the behavioral intentions of MaaS during public health events - Luo, Hang; Ma, Shoufeng; Tian, Junfang; Dong, Hongming (Frontiers in Psychology, 2025)
IntroductionMobility as a Service (MaaS) integrates various modes of transportation, provides personalized travel services for travelers, and improves the efficiency of traditional travel modes. To examine the mechanisms underlying the impact of sudden public health events on the behavioral intentions to use MaaS and provide theoretical support for the sustainable development of MaaS, this research investigates the Beijing MaaS program as a case.MethodsA total of 630 questionnaires were collected. Theoretical model, sourced from the Unified Theory of Acceptance and Use of Technology (UTAUT) model, is employed to elucidate the influence of six variables—performance expectancy, effort expectancy, social influence, ambiguity tolerance, perceived health threat, and policy cognition—on the behavioral intentions of MaaS.ResultsThe results show that three variables from the UTAUT positively impact behavioral intention and that there is a significant mediating effect of policy cognition on the relationship between these variables and the intention to use. Travelers with a high level of ambiguity tolerance are more inclined to use MaaS, while the perceived health threat reduces the intentions.DiscussionMultigroup analysis revealed differences in effort expectancy, ambiguity Toleance, and perceived health threat among the various groups. The research findings may provide theoretical guidance and empirical evidence for the promotion strategies of MaaS and for the formulation of related policies.